LONG-TERM MORBIDITY OF AXILLARY LYMPH NODE DISSECTION: IMPLICATIONS FOR PATIENTS WITH CARCINOMA BREAST - Javaid, Rana Hassan; Bashir, Eitezaz Ahmed; Waqas, Ahmed (Journal of Ayub Medical College Abbottabad, 2011)
Background: To assess the long term complications of level II Axillary Lymph Node Dissection (AXLND) in patients with breast cancer and to see if they are high enough to warrant a Sentinel Lymph Node (SLN) biopsy in all patients presenting with carcinoma breast in our setup in Pakistan. Methods: This study was conducted at Surgical Unit IV, Department of Surgery, Combined Military Hospital, Rawalpindi. Upper, lower arm circumferences and body mass index were ascertained in post Modified Radical Mastectomy (MRM) with level II AXLND, in female patients who had undergone surgeries from 1992 to 2008. Patient’s perception of degree of lymph oedema, arm function and other symptoms like pain, tingling and numbness was noted. The number of lymph nodes removed, number of positive nodes and post operative radiotherapy were also recorded from the hospital records. Results: Thus upper arm circumference in 85.7% patients and lower arm circumference in 89.2% patients was within 2 Cm of the unaffected side. No, moderate and severe arm swelling was described by 83.35% of patients, 11.6% of patients and one patient respectively and 41.5% of patients describing some arm swelling had positive lymph nodes. Thus even if they had gone (SLN) biopsy, these patients would have had a subsequent AXLND. Over 94% of patients had either good or excellent arm function with most in the excellent range. Conclusion: The patients at significant risk for positive nodal may be better served with an AXLND rather than the SLN technique. Keywords: Breast carcinoma, Sentinel lymph node biopsy, Axillary Lymph Node Dissection